2013
DOI: 10.1007/s00595-013-0720-4
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial synovial sarcoma: a case report and review of the literature

Abstract: Primary pericardial synovial sarcoma is a rare disease. We herein report a case of synovial sarcoma that originated in the epicardium. A 13-year-old male visited our hospital with a fever and chest pain. Copious pericardial effusion and a large intrapericardial tumor were detected. An open-chest tumor resection was performed. A solid nodular tumor was observed in the pericardial cavity. The tumor was a polypoid mass that was pedunculated and grew from the inner surface of the pericardium near the origin of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…They are classified as biphasic, monophasic and poorly differentiated based on their histology. Among the pericardial synovial sarcomas, the biphasic type (composed of an epithelial component and a spindle-cell component) appears to be more common than the monophasic type (only spindle-cells) and the poorly differentiated type (small round cells) 2, 912 . Our patient had a monophasic variant with predominant spindle to oval cells in a fascicular pattern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are classified as biphasic, monophasic and poorly differentiated based on their histology. Among the pericardial synovial sarcomas, the biphasic type (composed of an epithelial component and a spindle-cell component) appears to be more common than the monophasic type (only spindle-cells) and the poorly differentiated type (small round cells) 2, 912 . Our patient had a monophasic variant with predominant spindle to oval cells in a fascicular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The real incidence of pericardial synovial sarcoma may be underestimated though, as the precise site of origin of such tumors can be difficult to determine. To date, to the authors’ knowledge, only 20 cases have been reported in the English literature 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pericardiocentesis and cytological analysis of pericardial fluid is usually non-diagnostic and lacks specificity 9. Imaging modalities are usually the cornerstone for diagnosis 8 10.…”
Section: Discussionmentioning
confidence: 99%